1979
DOI: 10.1093/ajcn/32.2.304
|View full text |Cite
|
Sign up to set email alerts
|

Uniformity of human milk

Abstract: Compositon of human milk was studied during the feed in six women, through-out the day in one woman on 3 consecutive days and in three women on 39 occasions during established lactation. The total lipid content varied in the course of suckling as well as diurnally in a regular and predictable manner, but the fatty acid composition of the lipid remained constant and was similar in the subjects examined. Fatty acid pattern of milk lipid of one woman supplementing her diet with unsaturated fats was studied. The c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

11
99
1
12

Year Published

1985
1985
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 187 publications
(123 citation statements)
references
References 17 publications
11
99
1
12
Order By: Relevance
“…Iron content of human milk is highest in early transitional milk (0.97 mg/l) (Lauber and Reinhardt, 1979) but decrease steadily during lactation, reaching a level of approximately 0.35 mg/l at 1 month of lactation to 0.20 mg/l at 6 months (Lemons et al, 1982;Lonnerdal, 1984). The diurnal variation in iron content of breastmilk tend to parallel those reported for fat content with significantly lower mean values in the early morning feeding compared to late evening feeding (Hall, 1979;Fransson and Lonnerdal, 1980). No significant correlations were found between maternal age, parity or previous history of lactation and the iron content of milk at each stage of lactation (Celada et al, 1982).…”
Section: Discussionmentioning
confidence: 83%
See 1 more Smart Citation
“…Iron content of human milk is highest in early transitional milk (0.97 mg/l) (Lauber and Reinhardt, 1979) but decrease steadily during lactation, reaching a level of approximately 0.35 mg/l at 1 month of lactation to 0.20 mg/l at 6 months (Lemons et al, 1982;Lonnerdal, 1984). The diurnal variation in iron content of breastmilk tend to parallel those reported for fat content with significantly lower mean values in the early morning feeding compared to late evening feeding (Hall, 1979;Fransson and Lonnerdal, 1980). No significant correlations were found between maternal age, parity or previous history of lactation and the iron content of milk at each stage of lactation (Celada et al, 1982).…”
Section: Discussionmentioning
confidence: 83%
“…Studies on lactating women of varying ethnic origins have shown that breastmilk iron is independent of their hemoglobin (Hb) and iron status (Loh and Sinnathuray, 1971). Breastmilk iron and lactoferrin levels are known to vary according to the type of milk, age of lactation and diurnal variation (Hall, 1979;Houghton et al, 1985). Considering the varying epidemiological factors and the high degree of malnutrition and anemia in the lactating mothers of developing countries, the need for such a study was felt.…”
Section: Introductionmentioning
confidence: 99%
“…A ®rst explanation for the inconsistencies between these studies may be related to the timing of breast sampling. Although fat content in mature breast milk varies by the duration of breastfeeding and during the day (Harzer et al, 1983), and during a nursing (Jensen et al, 1992;Hall, 1979), the fatty acid composition of the lipid fraction remains fairly constant in these time aspects (Jensen et al, 1992;Hall, 1979;Lammi-Keefe et al, 1990). Therefore, we do not believe that differences between studies could be explained by differences in the timing of breast milk sampling.…”
Section: Discussionmentioning
confidence: 91%
“…Long the purview of nutritionists and clinicians, investigations of milk composition are increasingly conducted by anthropologists and human biologists. These studies forgo the assumption that milk is passively transferred from mother to infants (Hall, 1979), instead reframing human milk as a dynamic evolutionary and cross-cultural phenomenon that links mothers and infants. The nuances of the direct physiological exchange-from potential developmental signaling to the life history trade-offs of mothers and infants-have considerable potential for understanding population and individual biological variability for a host of phenotypes.…”
Section: Introductionmentioning
confidence: 99%